A rare case of multiple neuromuscular variations in the axilla and arm - Pei Wang; Yu-Lin Hsien; Wan-Yi Ho; Chun-Chih Liu; Tin-Hsin Hsiao; 王霈; 謝侑霖; 何宛怡; 劉俊馳; 蕭廷鑫 (Kaohsiung Journal of Medical Sciences, 2011)
During the dissection of a 73-year-old embalmed male cadaver, we noted unusual variations in the flexor compartment of the upper limb—bilateral axillary arch muscles, a three-headed biceps brachii muscle with two supernumerary bellies—and variations in the origin of the musculocutaneous and median nerves from the brachial plexus. The morphological and clinical significance of this unique coexistence of multiple neuromuscular variations are discussed.